PEMBERDAYAAN KELUARGA SEBAGAI PENDAMPING YANG SABAR, BERJUANG DAN BERTAHAN (SAJUTA) DALAM MERAWAT LANSIA DENGAN HIPERTENSI DI DESA CINANJUNG TANJUNGSARI SUMEDANG (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2023)
Data from the Global Status Report on Non Communicable Diseases 2019 from WHO states that 40% of developing countries have hypertension sufferers, in the Southeast Asian region 36% of adults suffer from hypertension. (Ministry of Health R1, 2019) and more than 25% of Indonesians suffer from hypertension, but only 10% know that they have hypertension. (Ministry of Health RI, 2018). Proper management of hypertension can prevent complications from hypertension (Ministry of Health, 2019). In the management of hypertension, the elderly need support and motivation from family, health workers and cadres (Sudiantara et al., 2022). The purpose of this community service activity is to increase the knowledge and skills of cadres and families in caring for the elderly with hypertension patiently, fighting and surviving (SAJUTA). The method used in this community service activity is to provide training to cadres and assistance to families about caring for elderly hypertension patiently, fighting and surviving (SAJUTA). The target of this activity is 20 cadres and 20 families of hypertensive elderly. The location of the activity is the village of Cinanjung Tanjungsari Sumedang. The results of the activity showed an increase in knowledge of cadres from an average score of 76.4 to 86.7 (up 10.3 points) and an increase in family knowledge from 50.5 to 64.5 (up 14 points). Cadres and families are expected to be able to care for the elderly with hypertension so that the elderly's blood pressure is controlled and avoid complications.